Settlement of Islamic finance disputes in the United Arab Emirates - Mohd. Zain, Nor Razinah; Hassan, Rusni (Routledge, 2019)
The concept of Islamic finance was considered as a wishful dream almost three decades ago. Today, more than 300 Islamic financial institutions are operating around the globe. By 2020, Islamic finance assets are estimated to reach $3.2 trillion in value. Their clientele are not confined to citizens of Muslim countries only, but are spread over Europe, the United States of America and the Far East. Muslims now have the opportunity to invest their financial resources in accordance with the ethics and philosophy of Islam. At the same time, Islamic finance offers an alternative for the customers of conventional finance. The first thorough studies devoted to the establishment of Islamic financial institutions (referred to hereafter as ‘Islamic Banks’) appeared in the 1940s. Although Muslim owned banks were established as early as in the 1920s and 1930s, they adopted similar practices to conventional banks. In the 1940s and 1950s, several experiments with small Islamic Banks were undertaken in Malaysia and Pakistan. The first great success was the establishment of an Islamic Bank in the Egyptian village of Mit Ghamr, in 1963. Other successes include the establishment of the Inter-Governmental Islamic Development Bank in Jeddah in 1975 and a number of Islamic Banks, such as the Dubai Islamic Bank, the Kuwait Finance House and the Bahrain Islamic Bank in the 1970s and 1980s. In South East Asia, Malaysia became the first country that introduced Islamic finance with the establishment of Bank Islam Malaysia Bhd. in 1983. Commercial banks have also realized the potential of this new field, and a number of major worldwide institutions have adopted Islamic banking and finance as a significant mechanism for diversified growth.